A Comprehensive Rheumatological and Immunological Approach to Diagnosis of Psoriatic Arthritis - Koarada, Syuichi (Cambridge Scholars Publisher, 2020)
This book provides a detailed investigation of psoriatic arthritis (PsA), a chronic rheumatic disease that involves joints, entheses and skin. Although PsA has been considered as a milder form of arthritis, in the past decade, it has been proven to be a potentially serious disease like rheumatoid arthritis (RA). Radiographic findings, clinical presentation and laboratory tests reveal that PsA is a distinct joint disorder from RA. However, early diagnosis of PsA is difficult. The book illustrates how to accurately diagnose the disease through a systematic approach to PsA. It presents typical an.